The Effect of Labor Market Shocks across the Life Cycle - Kjell G. Salvanes; Barton Willage; Alexander Willén (Institute of Labor Economics (IZA), 2022)
Adverse economic shocks occur frequently and may cause individuals to reevaluate key life decisions in ways that have lasting consequences for themselves and the economy. These life decisions are fundamentally tied to specific periods of an individual's career, and economic shocks may therefore have substantially different impacts on individuals - and the broader economy - depending on when they occur. We exploit mass layoffs and establishment closures to examine the impact of adverse shocks across the life cycle on labor market outcomes and major life decisions: human capital investment, mobility, family structure, and retirement. Our results reveal substantial heterogeneity on labor market effects and life decisions in response to economic shocks across the life cycle. Individuals at the beginning of their careers invest in human capital and relocate to new labor markets, individuals in the middle of their careers reduce fertility and adjust family formation decisions, and individuals at the end of their careers permanently exit the workforce and retire. As a consequence of the differential interactions between economic shocks and life decisions, the very long-term career implications of labor shocks vary considerably depending on when the shock occurs. We conclude that effects of adverse labor shocks are both more varied and more extensive than has previously been recognized, and that focusing on average effects among workers across the life cycle misses a great deal.
Keywords: I20; J63; 330; labor supply; human capital; education; fertility; family formation; mobility; retirement; disability; economic shocks; job displacement